Analysis of Writing Skills Learning Using Riau Cultural Literacy-based Modules in Elementary Schools - Mulyani, Eva Astuti; Rismawati, Evi; Wardani, Citra Yulia; Ramadan, Rully Rachmawati (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2024)
This research aims to analyze writing skills learning using Riau culture-based modules in elementary schools. This research approach is descriptive qualitative. Data was obtained through observation, interviews and document analysis. The research results show that there are variations in the implementation of learning modules between schools, with some schools already using modules that integrate digital technology, while other schools still use conventional methods. Integrating local culture in learning to write has a positive impact on students' understanding of the richness of their own culture. However, the fact is that Riau culture has not been utilized optimally as a learning resource. This research suggests developing a more varied Riau Cultural Literacy E-Module so that it can be implemented better